2‐Chloro‐4‐nitrobenzoic acid as a coformer with pharmaceutical cocrystals and molecular salts. Issue 8 (21st July 2020) - Lemmerer, Andreas
Abstract : Three new cocrystals and two molecular salts of the pharmaceutically relevant 2‐chloro‐4‐nitrobenzoic acid molecule are reported. Abstract : A series of five binary complexes, i.e. three cocrystals and two molecular salts, using 2‐chloro‐4‐nitrobenzoic acid as a coformer have been produced with five commonly available compounds, some of pharmaceutical relevance, namely, 2‐chloro‐4‐nitrobenzoic acid–isonicotinamide (1/1), C7 H4 ClNO4 ·C6 H6 N2 O, 2‐chloro‐4‐nitrobenzoic acid–3, 3‐diethylpyridine‐2, 4(1 H, 3 H )‐dione (2/1), 2C7 H4 ClNO4 ·C9 H13 NO2, 2‐chloro‐4‐nitrobenzoic acid–pyrrolidin‐2‐one (1/1), C7 H4 ClNO4 ·C4 H7 NO, 2‐carboxypiperidinium 2‐chloro‐4‐nitrobenzoate, C6 H12 NO2 − ·C7 H3 ClNO4 −, and (2‐hydroxyethyl)ammonium 2‐chloro‐4‐nitrobenzoate, C2 H8 NO + ·C7 H3 ClNO4 − . The coformer falls under the classification of a `generally regarded as safe' compound. All five complexes make use of a number of different heteromeric hydrogen‐bonded interactions. Intermolecular potentials were evaluated using the CSD‐Materials module.